THU0395 MUSCLE STRENGTH COMPROMISE IN YOUNG AXIAL SPA PATIENTS: PRELIMINARY RESULTS FROM MYOSPA STUDY. (June 2019) - Neto, Agna; Torres, Rita Pinheiro; Domingues, Lucia; Teixeira, Diana; Rodrigues-Manica, Santiago; Marona, José; Lopes, Carina; Gomes, João Lagoas; Costa, Tiago; Gonçalves, Maria João; Silva, Inês; Carreto, Paula; et al.
Abstract : Background: Pain and stiffness are characteristic clinical features of axial Spondyloarthritis (axSpA), leading to functional impairment. Patients describe beneficial effects of physical activity, suggesting a possible involvement of muscle tissue. Body composition data in young axSpA patients with short disease duration are scarce and its implications in muscle strength are not yet clarified. Objectives: The purpose of this study is to assess the muscle strength and body composition of different body segments (trunk, upper and lower limbs), in patients with axSpA and to compare them with healthy controls. Methods: Patients with clinical diagnosis of axSpA meeting the ASAS classification criteria, aged 18 to 50 years, with symptoms duration ≤ 10 years, were included in this study. Healthy individuals matched by gender and age (1:1) were used as control group (HC). Muscle strength was measured by resisted hand-held dynamometer performed by a single reader, in three different body segments: trunk, upper and lower limbs (on both sides). The mean strength of right and left, upper and lower limbs, was calculated and used in the analysis. Strength of each body segment was also normalized to the total lean mass (LM) of the respective segment. Body composition was measured by octapolar multifrequency bioelectrical impedance analysis (InBody770). Physical activity was assessed by the International Physical Activity Questionnaire (IPAQ). Fisher's exact test or chi-square test and Mann-Whitney U test were used to compare differences between groups. Results: A total of 27 axSpA patients and 27 HC were included. Mean age was 36.5 ± 1.0 years, 67% were males. There was no significant difference between both groups in terms of age, gender, body mass index and physical activity. AxSpA patients had a mean symptoms duration of 7.0 ± 0.9 years. AxSpA patients had lower muscle strength in the upper limbs (50.55 ± 31.60 vs 71.70±31.41 p =0.023) and lower limbs (52.25±18.45 vs 59.83±9.75, p =0.001), compared to HC. Trunk muscle strength did not show any difference between groups (59.10±26.1 vs 56.45±11.2, p =0.856). There were no significant differences in LM and body water, between both groups, for each segment (upper limbs, lower limbs and trunk). Fat mass was significantly higher in the trunk (10.90±8.80 vs 8.10±5.83, p =0.035) and upper limbs (1.40±1.35 vs 0.88±1.0, p =0.05) of axSpA patients, but not in the lower limbs (3.10±1.90 vs 2.45±1.68, p =0.157). Normalized appendicular muscle strength was lower in axSpA patients (upper limbs: 18.63±8.25 vs 21.21±5.92, p =0.018) (Table). Conclusion: Young patients with short duration have reduced appendicular muscle strength, compared to HC, with no differences in LM, suggesting a possible muscle dysfunction. Further studies are needed to confirm these findings and understand the underlying pathophysiological mechanisms. Disclosure of Interests: Agna Neto: None declared, Rita Pinheiro Torres: None declared, Lucia Domingues: None declared, Diana Teixeira: None declared, Santiago Rodrigues-Manica Grant/research support from: Novartis, MSD, Speakers bureau: Novartis, José Marona: None declared, Carina Lopes: None declared, João Lagoas Gomes: None declared, Tiago Costa: None declared, Maria João Gonçalves: None declared, Inês Silva: None declared, Paula Carreto: None declared, Walter Castelão: None declared, Margarida Mateus: None declared, Manuela Costa: None declared, Sandra Falcão: None declared, Ana Filipa Mourão: None declared, Atlas Sardoo: None declared, Sara Maia: None declared, Conceição Calhau: None declared, Jaime Branco: None declared, Fernando Pimentel dos Santos Grant/research support from: From Abbvie and Novartis, Speakers bureau: Abbvie, Novartis, Pfizer, Biogen,